2017
DOI: 10.4236/aid.2017.74015
|View full text |Cite
|
Sign up to set email alerts
|

Enteroparasitoses in Patients with Rheumatoid Arthritis

Abstract: Background: Patients with rheumatic diseases have profound alterations in the immune system as a result of underlying diseases and the treatments used, which increases the risk of occurrence and severity of infections, including enteroparasitosis. The current treatment for rheumatoid arthritis involves immunosuppressive therapies powerfully needed for screening infectious processes. The prevalence of parasitic infections in rheumatoid arthritis patients is not currently documented in literature. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…histolytica , and Ent. coli has been related to poor health scales and fatigue ( 20 ), but not with the parameters of disease's clinical activity ( 18 ), similar to what was found in this study. Nevertheless, B. hominis has been particularly associated with reactive RA in four clinical cases ( 13 , 17 , 19 ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…histolytica , and Ent. coli has been related to poor health scales and fatigue ( 20 ), but not with the parameters of disease's clinical activity ( 18 ), similar to what was found in this study. Nevertheless, B. hominis has been particularly associated with reactive RA in four clinical cases ( 13 , 17 , 19 ).…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of infection by intestinal protozoa in subjects with rheumatic diseases has been previously reported to be particularly high (25–30%) ( 48 ), when compared to that reported in Mexican population ( 49 ) and asymptomatic ( 50 ). In the present study, we found that 50% (9/18) of the individuals with RA recruited were positive for intestinal protozoa, similarly reported in an Egyptian population with RA ( 51 ), and higher than the report of Jimenez-Balderas et al ( 48 ) for patients with RA in Mexico City [25%, (3/12)], and also the one reported for patients with RA in Brazil [11.9%, (8/67)] ( 20 ). These differences could be explained by sociodemographic factors that influence risk of parasitic infection, such as living in rural areas, lacking basic services (drinking water, for example), and the number of inhabitants per household ( 52 ), poor personal hygiene ( 50 ), and living with pets ( 48 , 53 ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations